Osteosynthesis of bilateral Vancouver B2 periprosthetic femoral fracture after a bilateral RM® total hip arthroplasty at 24 and 21-years follow-up: A case report - Ferreira, ID (2019)
INTRODUCTION: The management of periprosthetic femoral fractures following hip arthroplasty is challenging, and the choice between osteosynthesis of the fracture and the revision of the prosthesis is still matter of discussion. CASE REPORT: In a 81-year-old male patient, a bilateral Vancouver type-B2 periprosthetic femoral fracture with stem loosening occurred after an accidental fall. The patient had severe medical comorbidities. The radiographic study showed a bilateral Robert Mathys cementless total hip arthroplasty at 24 and 21-years follow-up. The fractures were treated with open reduction and fixation with locking compression plates. Bicortical fixation of the loose stem was obtained by the screws of the locking plate, due to the polymeric composition of the isoelastic femoral stem. Both fractures sites were augmented with bone allografts. At follow-up period of 12 months, the X-rays showed bone union of both fractures and bilateral stable stem fixation. The patient expressed high degree of satisfaction with surgery result. DISCUSSION: The standard treatment for Vancouver type-B2 periprosthetic femoral fractures is the removal of the loose implant, fixation of the fracture, and implantation of a new revision femoral stem. However, the implantation of two long revision hip prostheses is a major operation for an older patient with precarious health condition, which can contribute to higher risk of medical and prosthetic complications. CONCLUSION: In older patients with multiple comorbidities, the use of locking plates can be a valid treatment of bilateral Vancouver B2-periprosthetic femoral fractures following RM® cementless isoelastic stem, as an alternative surgical option to femoral stem revision.